Estudio fitoquimico preliminar y actividad fungicida de corteza de maytenus urquiolae mory (celastraceae) - Fernandez de la Torre, A.=700 1 Nogueiras Lima, C.; Romeu Carballo, C.
(Es, En)
Ilus., 17 ref.
Keywords: CELASTRACEAE; CORTEZA; COMPOSICION QUIMICA; METABOLITOS SECUNDARIOS; TAMIZADO; BIOQUIMICA; CUBA